The decreased self-renewal potential of NPCs during human embryonic brain development with reduced activity of MAPKs. - Zhao, L. Y.; Jiao, Q.; Xu, X.; Yang, P. B.; Song, T. S.; Huang, C.; Zhang, J. F.; Liu, Y. (Cellular and Molecular Biology, 2012)
Study of neural progenitor cells (NPCs) is important for treatment of degerative diseases in central nervous system. One of the key questions in NPCs transplantation therapy is about the understanding of which stage of the NPCs in brain development is ideal. Herein we investigated survival, proliferation and apoptosis of NPCs from 12 w, 16 w and 20 w human embryonic brain, meanwhile, the phosphorylation of mitogen-activated protein kinases (MAPKs) signaling were analyzed. The results showed that the survival, proliferation and cell division of 16 w and 20 w human NPCs significantly decreased comparing with 12 w human NPCs in vitro; and the NPCs apoptosis remarkably increased. Phosphorylation of ERK1/2 of 16 w and 20 w NPCs significantly decreased comparing with 12 w human NPCs, however phosphorylation of p38 MAPK increased. NPCs proliferation increase when ERK1/2 signaling is activated by PMA.. The results demonstrated that self-renewal potential of NPCs decreased in culture during human embryonic brain development, the activity of ERK signaling pathway were decreased, and suggest NPCs from 12-week fetuses might be better donor for cell transplantation during the period of 12-20 weeks because of their advantage on survival and proliferation.